Advances in hepatitis E – II: Epidemiology, clinical manifestations, treatment and prevention. (1st September 2016) - Goel, Amit; Aggarwal, Rakesh
ABSTRACT: Introduction : Infection with hepatitis E virus (HEV) is the commonest cause of acute hepatitis worldwide. This infection, with fecal-oral transmission, was previously thought to be limited to humans residing in developing countries with poor sanitation, spreading via contaminated drinking water. In recent years, our understanding of epidemiology and clinical spectrum of this infection have changed markedly. Areas covered : This article reviews the epidemiology, including routes of transmission, and clinical manifestations of HEV infection around the world. In addition, recent findings on transmission-associated HEV infection, extrahepatic manifestations of hepatitis E and chronic infection with HEV, and treatment and prevention of this infection are discussed. Expert commentary : HEV infection has two distinct epidemiologic forms and clinical patterns of disease: (i) acute epidemic or sporadic hepatitis caused by fecal-oral (usually water-borne) transmission of genotype 1 and 2 HEV from a human reservoir in areas with poor hygiene and frequent water contamination, and (ii) infrequent sporadic hepatitis E caused by zoonotic infection, possibly from an animal source through ingestion of undercooked animal meal, of genotype 3 or 4 virus. In disease-endemic areas, pregnant women are at a particular risk of serious disease and high mortality. In less-endemic areas, chronic infection with HEV among immunosuppressed persons is observed. HEV can also be transmitted through Transfusion of blood and blood products. Ribivirin treatment is effective in chronic hepatitis E. Two efficacious vaccines have been tried in humans; one of these has received marketing approval in its country of origin.